Numerical Simulation of Basic Support Parameters for the 2304 Working Face Entry in the Main Coking Coal Mine - Gao, Jianan (International Journal of Natural Resources and Environmental Studies, 2025)
This study addresses the complex geological conditions of the upper gateway in the 2304 working face of Anyang Main Coking Coal Mine. Using the UDEC numerical simulation method, the displacement and stress distribution laws of surrounding rock under different support conditions were analyzed. The results show that reasonable support measures can effectively control roadway deformation and improve surrounding rock stability, providing a theoretical basis for similar engineering projects.